KAJIAN LAJU SEDIMENTASI WADUK PLTA KOTO PANJANG DALAM UPAYA MELESTARIKAN KESINAMBUNGAN ENERGI LISTRIK PROVINSI RIAU - Imam Suprayogi; Bochari - (Universitas Pasir Pengaraian, 2010)
Reservoirs in the wet tropics generally have a fairly rapid sedimentation problems. Not infrequently happens that has begun to operate reservoirs showed symptoms of increased sedimentation. This paper aims to find and solve problems that arise due to the high rate of sedimentation and deposition in the Koto Panjang reservoir hydropower, Riau province in an effort to preserve the continuity of electric energy in Riau Province. Method approach taken to describe the pattern of relationship between flow rate, sedimentation and the characteristics of the reservoir as a basis for watershed management in the upstream using regression equations developed by Singh and Chen (1982). The results of the investigation show that the land area (Af) in the upstream has a dominant influence on the rate of annual sediment entering the Koto Panjang reservoir hydropower. For the reduction of land area by 15%, an increase in the volume of sediment from 1.4 million m3 to 11.4 million m3.